Internalisasi Nilai Soft Skills dalam Pelatihan Dasar Calon Pegawai Negeri Sipil di Balai Besar Pelatihan Kesehatan Jakarta - Syarief, Yunita Iriani (Jurnal Inspirasi, 2022)
Abstract This study aims to: 1) describe the application of the soft skill value internalization approach in strengthening the Basic Training Model (Latsar) for Candidates of Civil Servants (CPNS) Class III at the Jakarta Health Training Center (BBPK Jakarta); 2) Knowing the opinions and responses of the Latsar Participants towards the application of the Internalization approach to the soft skill value. The research was conducted using a qualitative approach with a case study method for the Implementation of the Batch I Latsar 2019. Data collection was carried out using observation, interviews, and document studies. The collected data is reduced, presented and analyzed to draw conclusions. For the validity of the data, source triangulation was used. The results showed that: 1) BBPK Jakarta implemented an internalization approach soft skill values to strengthen the implementation model of the Class III CPNS Latsar with four approaches, namely: cognitive, exemplary, conditioning, and habituation. Through data processing thought, heart, sport, taste and initiative, which are integrated into the organizational culture, the four approaches are applied simultaneously, closely intertwined with one another and mutually supportive, complemented by layered control and supervision functions; 2) Of the 40 Latsar participants, almost all understood and accepted the value internalization approach that was applied, agreed and admitted that they had a deep impression on the implementation of the Latsar held by BBPK Jakarta. They also know the lessons learned during the training at BBPK Jakarta. Criticisms and suggestions given include: standardization of Widyaiswara Competencies, too short time, so the schedule is tight, learning methods and complaints for one example that’s not good.